Peningkatan Literasi Analisa Laporan Keuangan: Analisis Pemberian Pinjaman - Nuha, Sukma Uli; Reviandani, Wasti; Vilantika, Elok (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Community Service was held for students of the Faculty of Economics and Business, Universitas Muhammadiyah Gresik who taught the Financial Report Analysis course entitled